A Study on the Change of Functions of Kinari Village’s Rumah Gadang - Zhang Jingling (Andalas International Journal of Socio-Humanities, 2019)
This paper will present the real condition of traditional house in Nagari Kinari and try to analyze the change of the traditional house function as well as its factors. The study uses a qualitative approach to identifying and collecting field data through the fieldwork in Nagari Kinari, Solok. The result shows traditional houses in Kinari have changed its functions dramatically. These changes occur due to social changes, including changes in family structure, economic income, the national education system and personal awareness, and also differences in understanding of traditional culture.